Chinese medicine for headaches in emergency department: a retrospective analysis of real-world electronic medical records - Zhenhui Mao; Shirong Wu; Yuzhen Fan; Jingbo Sun; Shaohua Lyu; Qiaozhen Su (Frontiers in Neurology)
BackgroundHeadaches are common complaints in the emergency department (ED) and have raised concern about acute medication overuse. Chinese medicine is a major complementary and alternative medicine in China and effective for headaches. This study aims to summarize characteristics of headache patients at EDs and the utilization of Chinese medicine for headache managements in EDs.MethodsThe study conducted a retrospective analysis based on existing electronic medical records at EDs from four branches of Guangdong Provincial Hospital of Chinese Medicine. Only complete medical records with a first diagnosis of headache within the specified timeframe were included. Data was extracted, screened and standardized using a structured approach. Descriptive analyses and Apriori algorithm-based association rules were employed for the study.ResultsA total of 3,355 medical records were analyzed, with over 86% of headaches classified as non-urgent. Approximately 97% of the patients received a general diagnosis of headaches without further classification. Hypertension was the most prevalent concomitant diagnosis, affecting 27.42% of the patients. Western medicine was prescribed to 66% of the patients for headaches and co-existing conditions, while each type of acute medication was prescribed to fewer than 10% of the patients. Conversely, over one-third of the patients utilized headache-specific patented Chinese herbal medicine products. Additionally, oral and topical Chinese herbal medicine treatments were also administered for headaches in the emergency departments.ConclusionThe majority of headaches consulting in the EDs were non-urgent and treated with various forms of Chinese medicine, alone or in conjunction of western medicine. Chinese herbal medicine may be promoted as alternatives to Western acute medications for treating benign headaches.